The Think Pair Share (TPS) Learning Model Is An Effort To Increase Motivation For Success and Learning Outcomes of Students of The Faculty Of Teacher Training And Education, Lambung Mangkurat University. - Devita Oky Fiara; Monry Fraick Nicky Gillian Ratumbuysang; Baseran Nor; Ananda Setiawan (Diversity: Jurnal Ilmiah Pascasarjana, 2023)
This study aims to find out the think pair share learning model  to increase motivation for success and student learning outcomes at the Faculty of Teacher Training and Education, Lambung Mangkurat University. The method used in this study is classroom action research with collaborative PTK types. The research subjects consisted of 70 students of Biology Education, Faculty of Teacher Training and Education, Lambung Mangkurat University, Banjarmasin who took entrepreneurship courses for the 2022 academic year (odd semester). Data collection techniques use interviews, observations, learning outcomes tests and online questionnaires for validity and reliability tests. Data analysis uses descriptive analysis techniques, normality tests, data linearity tests and hypothesis testing (simple linear regression, t test). Based on the results of the study, it was concluded from cycles I and II that there was an increase in motivation from the success of the Think Pair Share (TPS) model by 69.88%, which is still quite good. The success  of the Think Pair Share (TPS) model which is applied in improving student learning outcomes consisting of 2 cycles is carried out in accordance with research procedures, namely, planning, implementation, observation and reflection so that there is an increase of 11.09% which is still very low.